The dream of transcending the human through the digital matrix: A relational critique - Pierpaolo Donati (Scientia et Fides, 2019)
The advent of the digital era brings with it the dream of ‘transcending the human’ through the most sophisticated AI / robot technologies. The Author argues that the concept and practices of ‘transcendence’ are deeply ambiguous, since on the one hand they simply aim to overcome the weaknesses, limits and fragility of the human, while on the other hand they modify the human by selecting its specific qualities and its causal properties in a way to generate beings ‘other than human.’ As a matter of fact, post / trans-humanist ideologies, instead of strengthening the human, lead to its dehumanization because they imply the denial of the characteristics that are uniquely human and / or those that constitute human nature. To understand when new digital technologies enhance the human or distort it, it is necessary to analyze and evaluate social processes on the basis of a relational vision that shows us which human relationships emerge from the use of technologies.